Effect of long-term Tillage and Nitrogen Fertilization Residue on Soil Biochemical Properties and Cowpea Yield - Afriliyanti, Rizki; Yusnaini, Sri; Karyanto, Agus; Hapsoro, Dwi; Niswati, Ainin; Utomo, Muhajir (UNIVERSITY OF LAMPUNG, 2021)
Sustainable soil management practices must enhance or maintain soil quality and crop yields. The objective of this experiment was to study the effect of long-term (32 years) tillage system and nitrogen fertilization residue on soil biochemical properties and cowpea (Vigna unguiculata) yields. This research was conducted using four replications, a factorial experiment arranged in a randomized block design. The first factor was tillage systems consisting of intensive tillage (T1) and no-tillage (T2) and the second factor was nitrogen fertilization residue (N) consisting of N1 (0 kg N ha-1) and N2 (200 kg N ha-1). Data were analyzed using analysis of variance; if there was a significant difference will be continued with the Least Significant Difference (LSD) test at 5%. Principal Component Analysis (PCA) determined the relationship among observed variables. The results showed that no-tillage could give better results on soil respiration and soil bacteria and fungi population than intensive tillage. Lower soil pH was found at 200 kg N ha-1 fertilizer residue than control (without N fertilizer). The cowpea growth and yields were high at long-term N1T2 and N2T1 treatment. Principal component analysis showed an interrelationship among soil biochemical properties, growth, and yield of cowpea.